Options trade - Pantić, Nemanja; Leković, Мiljan (Hotel and Tourism Management, 2013)
F?rward derivative market is a segment of financial market. The business on this market is done by means of financial and commodity derivatives through forward contracts. Financial derivatives depend on the growth of scale and the importance of forward operations on financial markets. Options as specific contracts give the holder the right, without obliging him, to buy or sell a certain amount of assets at a specified time in future at a previously agreed price. Options market is the most dynamic segment of the already dynamic securities market. Options are traded in the same way as futures; the only difference is the necessary security. The option buyer pays immediately the full amount of the premium to the option seller. He does not claim any benefit nor is the subject to any call of a clearing house to provide security.